1999
DOI: 10.1161/01.hyp.34.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium and Cardiovascular Risk Factors and Diseases

Abstract: Abstract-Total serum calcium levels were measured in 12 865 men and 14 293 women, between the ages of 25 and 97 years, in the Tromsø Study during 1994 and 1995. With the use of a sex-specific multiple linear regression model with age, calcium, body mass index, cholesterol, HDL cholesterol, triglycerides, systolic and diastolic blood pressure, and pulse as possible covariates, serum calcium was significantly (PϽ0.001) and positively associated with systolic and diastolic blood pressure, serum cholesterol, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
117
3
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 27 publications
11
117
3
2
Order By: Relevance
“…More recently, a prospective study by Lind et al 10 found that serum calcium was an independent risk factor for myocardial infarction in a cohort of Swedish middle-aged men. In another Swedish study, Jorde et al 9 also found a similar association in a group of 12 865 men but not in women.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…More recently, a prospective study by Lind et al 10 found that serum calcium was an independent risk factor for myocardial infarction in a cohort of Swedish middle-aged men. In another Swedish study, Jorde et al 9 also found a similar association in a group of 12 865 men but not in women.…”
Section: Discussionmentioning
confidence: 66%
“…8 Kesteloot and Geboers 2 also noticed that the blood pressure-serum calcium relationship was stronger in younger compared with older men. More recently, elevated serum calcium was found to be a predictor, 9 as well as an independent prospective risk factor, 10 for myocardial infarction in middle-aged men. All of the above studies involved Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…(40) However, serum calcium and/or phosphate concentrations have been associated with increased carotid artery plaque thickness (1) and increased incidence of cardiovascular events and death in large retrospective (3,4) and prospective cohorts (2,41) in the general population. Primary hyperparathyroidism is another condition with increased serum calcium concentrations and has been associated with increased risk of cardiovascular events and death, (5,6) although evidence for increased vascular calcification is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Serum calcium concentrations are positively associated with increased carotid artery plaque thickness (1) and with increased incidence of myocardial infarction (MI) and death. (2)(3)(4) An increased risk of cardiovascular events and death also has been reported in primary hyperparathyroidism, a condition in which serum calcium is elevated. (5,6) In patients with renal failure, calcium supplements accelerate vascular calcification and increase mortality in both dialysis and predialysis populations.…”
Section: Introductionmentioning
confidence: 99%
“…In epidemiological studies, serum calcium has been found to increase with increasing levels of systolic and diastolic BP. 1 Serum calcium has also been found to correlate with serum cholesterol, BMI and thus metabolic syndrome. 2 Recently, serum calcium has been reported to be independent risk factor for myocardial infarction in middle aged men.…”
mentioning
confidence: 99%